College and University Faculty Perceptions Towards Carrying Concealed Firearms on Campus - Verrecchia, P.J.; Hendrix, Nicole (International Journal of Criminology and Sociology, 2017)
This study uses a survey of university and college faculty members at two schools in the eastern United States to investigate their attitudes towards qualified faculty members and students carrying concealed firearms on their campuses. We found that faculty members who own a gun and are politically conservative were in favor concealed carry for qualified students and faculty, while liberal faculty member who are not gun owners were not.